PENGARUH PENGGUNAAN HANDPHONE TERHADAP MINAT MEMBACA BUKU PELAJARAN PADA PESERTA DIDIK KELAS V DI SD NEGERI 3 PANJER - Goreti Rini Kristiantari, Maria; Chindytia, Chindytia; Diantari Widana, Ni Made; Triani Prashanti, Ni Komang; Ayu Nirmala Sari, Ni Putu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to analyze the impact of cell phone use on the reading habits of fifth-grade students at SD Negeri 3 Panjer. This study employed a quantitative approach with a correlational research design. A total of 28 students were selected as research subjects using a saturation sampling technique. The data were analyzed using a Likert-scale questionnaire, which was then evaluated using simple linear regression analysis, t-tests, and the coefficient of determination. The findings indicate a negative correlation between cell phone use and reading interest, although this correlation is not statistically significant. This is supported by a significance level of 0,145 > 0,05 and a calculated t-value (-1,503) that is smaller than the critical t-value (2,056). Furthermore, the coefficient of determination (R²) of 0,080 indicates that the variable of cell phone use accounts for only 8% of the variation in reading time, while the remaining 92% is determined by other variables not included in this study. Consequently, cell phone use is not a dominant factor influencing students’ reading habits.